2022
DOI: 10.3390/vaccines10081223
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Booster Strategies for Omicron SARS-CoV-2 Variant: Effectiveness and Future Prospects

Abstract: In the light of the lack of authorized COVID-19 vaccines adapted to the Omicron variant lineage, the administration of the first and second booster dose is recommended. It remains important to monitor the efficacy of such an approach in order to inform future preventive strategies. The present paper summarizes the research progress on the effectiveness of the first and second booster doses of COVID-19. It also discusses the potential approach in vaccination strategies that could be undertaken to maintain high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 94 publications
0
14
0
Order By: Relevance
“…7 ). Note, however, additional booster administrations of mRNA- and adenovirus-based vaccines have demonstrated increased neutralization toward Omicron, suggesting that activation of B cells against mutant SP/RBD epitopes could be accomplished by multiple vaccination doses [27] , [40] , [41] . Perhaps the underlying mechanism of greater reactivity to omicron with SP/RBD-based AKS-452 or with increased SP-based vaccine dosing may be related to the “original antigenic sin” phenomenon [42] .…”
Section: Discussionmentioning
confidence: 99%
“…7 ). Note, however, additional booster administrations of mRNA- and adenovirus-based vaccines have demonstrated increased neutralization toward Omicron, suggesting that activation of B cells against mutant SP/RBD epitopes could be accomplished by multiple vaccination doses [27] , [40] , [41] . Perhaps the underlying mechanism of greater reactivity to omicron with SP/RBD-based AKS-452 or with increased SP-based vaccine dosing may be related to the “original antigenic sin” phenomenon [42] .…”
Section: Discussionmentioning
confidence: 99%
“…40 However, the extent of protection against other remaining Omicron subvariants and other future SARS-CoV-2 variants is yet unclear. 41 …”
Section: Discussionmentioning
confidence: 99%
“…Many publications have evaluated the safety and immunogenicity elicited by homologous (same type of vaccine) or heterologous (different type of vaccines) COVID-19 vaccine booster. The heterologous prime-boost were demonstrated to be well tolerated, and the neutralizing antibody induction can be further enhanced compared to homologous prime-boost subjects [53][54][55]. For example, Atmar et al demonstrated that heterologous booster was able to induce 7-63 folds increase of neutralizing antibody, whereas homologous booster only showed 4-20 folds of increase in the study with different primary vaccination and booster combination [56].…”
Section: Plos Onementioning
confidence: 99%